Criminal law's asymmetry - Edwards, J (Routledge, 2017)
Criminal law confers powers and grants permissions. In doing so it does not treat all alike. Some state officials (and some of their delegates) are given powers and permissions that are much more extensive than those given to private persons (who are not delegates). As a result, steps taken to achieve criminal justice are often serious crimes if taken by members of the latter group, while being perfectly lawful when taken by members of the former. My question here is what justifies this asymmetry. I consider two candidate explanations. One appeals to impossibility. Another appeals to efficiency. While explanations of the first kind have become increasingly popular, I offer some reasons to doubt that they succeed. I conclude with a preliminary defence of a view that appeals to efficiency.